The Photodynamic Effect of LED-Magnetic Exposure to Photoinactivation of Aerobic Photosyntetic Bacteria - Astuti, Suryani Dyah (Indonesian Journal of Tropical and Infectious Disease, 2014)
All photosynthetic bacteria have a major pigment of bacteriochlorophyl and accessor pigment e.g. the carotenoids, which both have an important role in photosynthesis process. This study aim to explore the exogenous organic photosensitizer from photosyntetic bacteria for photodynamic therapy application. This study is an experimental research aiming to test the potential illumination of LED with wavelength 409, 430, 528 and 629 nm, and power optimization and time exposure LED-magnetic for optimum photo activation Rhodococcus growth. The reseach design use a factorial completely randomized design with factor of power and exposure time. The number of bacterial colonies grown measure using of Total Plate Count (TPC) methods. The result of anova test shows that irradiation treatment with LED 409 nm, 430 nm, 528 nm and 629 nm significantly affects on bacterial colony growth. LED 409 nm exposure has the greatest potential to boost the growth of bacterial colonies by 77%. LED exposure and the addition of 1.8 mT magnetic fieldincreases bacterial colony growth by 98%. Results of optimization of LED and magnetic fields show power 46 mW and a 40 minute (energy dose 110 J/cm2) optimum growth of bacterial colonies increase by 184%. So LED and magnetic illumination has potentially increased the viability of an aerob photosyntetic bacteria colonies.